Konsep Dasar Sejarah: Implementasinya Dalam Pembelajaran - Yussi Martha; Durratus Sa’diyah; Habib Maulana; Warto Warto (LPPM Politeknik Pratama, 2023)
History is a scientific discipline that involves the study of past events, the development of civilizations, and human interactions within them. History lessons that have been carried out so far have a bad image. The description of learning history is learning that is full of memorization, uninteresting, and boring. Whereas learning history can develop a sense of love, pride, and respect for cultural and historical heritage in students. Based on these reasons, the position of learning history is very important for the development of student character. So that learning is needed that is interesting and fun using the right strategies, methods and media. The aims of this research are among others to describe: understanding of history; historical education; the purpose of studying history; the benefits of studying history; the potential of historical education in shaping character; contextual, creative, and fun history learning in the classroom. The research method used is a qualitative descriptive research method based on the results of literature studies (library research). It is hoped that through fun and meaningful history lessons, students can gain deeper insight into the past, appreciate differences, and contribute to building a better future.